The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7322/jhgd.103004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Music During Physical Therapy Intervention in a Neonatal Intensive Care Unit: A Randomized Controlled Trial

Abstract: Introduction: Previous studies have shown music therapy as a way to improve the clinical status of premature infants, improving vital signs and decreasing crying episodes. Objective: Compare the effects of music on vital signs of premature infants undergoing respiratory physiotherapy. Methods: We performed a randomized clinical trial consisting of 26 premature infants, divided into control group (N=12) and study group (N=14), carried out in a Neonatal Intensive Care Unit. All newborn infants undergone standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
(50 reference statements)
1
13
1
1
Order By: Relevance
“…When considering oxygen saturation, however, the results differ from those presented in other articles that did not reach statistical significance in the increase of this variable (8,13,14) .…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…When considering oxygen saturation, however, the results differ from those presented in other articles that did not reach statistical significance in the increase of this variable (8,13,14) .…”
Section: Resultscontrasting
confidence: 95%
“…Results that are similar to those presented in several studies, but that do not address patients on NIV. The main results evidenced are reductions in respiratory frequency (8,13) and in heart rate (14) .…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has already evidenced that these interventions have a beneficial effect on PTI's brain development, mainly in the improvement of emotional regulation capabilities 14 . However, in the current review, conflicting results were found for outcomes such as HR, RR, satO2, BP, weight gain, circadian rhythm, feeding behaviour or rate and behavioural states 29,32‐34,37,39,40,46,49,51‐55 …”
Section: Discussionmentioning
confidence: 60%
“…A study conducted at the Touch Research Institute has showed that twenty minutes of massage every night for asthmatic children can help them to breathe better. This positive finding led to further questions on whether massage therapy, provided by parents, can improve the baby's mental, motoric and social development (Moran et al, 2015;Trivedi, 2015).…”
Section: Discussionmentioning
confidence: 99%